Study on Surfactants for the Removal of Water from Deliquification Natural Gas Wells to Enhance Production - Dorota Kluk; Teresa Steliga; Dariusz Bęben; Piotr Jakubowicz (Energies)
A major problem in natural gas production is the waterlogging of gas wells. This problem occurs at the end of a well’s life when the reservoir pressure becomes low and the gas velocity in the well tubing is no longer sufficient to bring the gas-related fluids (water and gas condensate) up to the surface. This causes water to accumulate at the bottom of the gas well, which can seriously reduce or even stop gas production altogether. This paper presents a study of the foaming of reservoir water using foaming sticks with the trade names BioLight 30/380, BioCond 30, BioFoam 30, BioAcid 30/380, and BioCond Plus 30/380. The reservoir waters tested came from near-well separators located at three selected wells that had undergone waterlogging and experienced a decline in natural gas production. They were characterised by varying physical and chemical parameters, especially in terms of mineralisation and oil contaminant content. Laboratory studies on the effect of foaming agents on the effectiveness of foaming and lifting of reservoir water from the well were carried out on a laboratory bench, simulating a natural gas-producing column using surfactant doses in the range of 1.5–5.0 g/m3 and measuring the surface tension of the water, the volume of foam generated as a function of time and the foamed reservoir water. The performance criterion for the choice of surfactant for the test water was its effective lifting in a foam structure from an installation, simulating a waterlogged gas well and minimising the dose of foaming agent introduced into the water. The results obtained from the laboratory tests allowed the selection of effective surfactants in the context of foaming and uplift of reservoir water from wells, where a decline in natural gas production was observed as a result of their waterlogging. In the next stage, well tests were carried out based on laboratory studies to verify their effectiveness under conditions typical for the production site. Tests carried out at natural gas wells showed that the removal of water from the bottom of the well resulted in an increase in natural gas production, ranging from 56.3% to 79.6%. In practice, linking the results of laboratory tests for the type and dosage of foaming agents to the properties of reservoir water and gas production parameters made it possible to identify the types of surfactants and their dosages that improve the production of a given type of natural gas reservoir in an effective manner, resulting in an increase in the degree of depletion of hydrocarbon deposits.